Effects of UV absorbers on cotton fabrics - (:unkn) unknown (My University, 2012)
Due to the ozone layer depletion, increased levels of UV rays start having wide ranging impacts on human health and welfare. Although the energy required to sustain life comes from the sun, acute or chronic overexposure to sunlight can lead to a variety of deleterious effects such as erythema (sunburn), photoaging, premalignant lesions and melanoma skin cancer. Clothing has the ability to protect the skin to an extent; but in many cases this protection may not be sufficient. The percentage of radiation transmitted by the fabric is a crucial factor that determines the level of protection. Fabrics that are treated with UV absorbers which have increased ability to attenuate light protect human skin from harms of solar radiation. UV absorbers can be incorporated into synthetic fibers in fiber spinning baths. They can also be applied as finishing agents. In this study, two types of 100% cotton fabrics have been used; twill 2/1 and rib 2/1. Following the application of preliminary processes, these fabric specimens were dyed with 0.1%Procion Brilliant Red HE-GXL (Dye-Star). UV absorbers were added before, during and after dyeing at the concentrations of 0 and 2 %. Transmittance values at 290-400 nm were measured. These values for undyed and dyed fabrics were used in the calculation of UPF and UV protection categories for each specimen were determined. Moreover, whiteness degrees of undyed specimens treated with UV absorbers were examined. The light fastness of dyed fabrics was also examined.
Keywords: Cotton fabrics; Light fastness; UV absorbers